2016
DOI: 10.1371/journal.pone.0160515
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Borderline Personality Disorder: A Systematic Review of the Perspectives of Consumers, Clinicians, Family and Carers

Abstract: PurposeLongitudinal studies support that symptomatic remission from Borderline Personality Disorder (BPD) is common, but recovery from the disorder probably involves a broader set of changes in psychosocial function over and above symptom relief. A systematic review of literature on both symptomatic and personal recovery from BPD was conducted including the views of consumers, clinicians, family and carers.Materials and MethodsA PRISMA guided systematic search identified research examining the process of recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 64 publications
(178 reference statements)
1
64
0
Order By: Relevance
“…This further supports the understanding that good psychosocial function is more difficult to achieve and sustain than symptomatic remission. There is a need to study psychosocial functioning more broadly, and expanding this area of research is also strongly supported by people with lived experience . Indeed, economic evaluations point to the benefits of treatment not only in terms of financial benefits for the patient and savings to the health system but also society gains from greater productivity and paying taxes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further supports the understanding that good psychosocial function is more difficult to achieve and sustain than symptomatic remission. There is a need to study psychosocial functioning more broadly, and expanding this area of research is also strongly supported by people with lived experience . Indeed, economic evaluations point to the benefits of treatment not only in terms of financial benefits for the patient and savings to the health system but also society gains from greater productivity and paying taxes .…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to study psychosocial functioning more broadly, and expanding this area of research is also strongly supported by people with lived experience. 14,15 Indeed, economic evaluations point to the benefits of treatment not only in terms of financial benefits for the patient and savings to the health system but also society gains from greater productivity and paying taxes. 16 In order to further develop treatments targeting function, a comprehensive understanding of what factors may contribute to persistent psychosocial impairment is required.…”
Section: Introductionmentioning
confidence: 99%
“…Little research has been conducted to explore perspectives of recovery in borderline personality disorder. A recent systematic review by Ng, Bourke, and Grenyer () aimed to understand how patients, clinicians, family, and carers perceived recovery from borderline personality disorder. The review identified 16 longitudinal quantitative studies with 11 unique cohorts, and three qualitative studies (Larivière et al., ; Katsakou et al., ; Holm & Severinsson, ) that examined recovery in borderline personality disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Ng et al. () found a greater emphasis on symptomatic remission as an indicator of recovery compared to other mental health problems. Despite the aims of the review, Ng et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation